2018
DOI: 10.1021/jacs.7b13598
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Chromophore–Protein Interactions through Linker Engineering To Tune Photoinduced Dynamics in a Biomimetic Light-Harvesting Platform

Abstract: Creating artificial systems that mimic and surpass those found in nature is one of the great challenges of modern science. In the context of photosynthetic light harvesting, the difficulty lies in attaining utmost control over the energetics, positions and relative orientations of chromophores in densely packed arrays to transfer electronic excitation energy to desired locations with high efficiency. Toward achieving this goal, we use a highly versatile biomimetic protein scaffold from the tobacco mosaic virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 69 publications
1
62
0
Order By: Relevance
“…Nanoscale control over chromophore position is challenging in proteins due to their structural complexity and limitations in mutagenesis. [20][21][22] Instead, synthetic model systems that position chromophores have been developed, including metal-organic frameworks, 8,23 viral proteins, [24][25][26] self-assembled molecular aggregates, [27][28][29][30] and conjugated polymers. 31 However, these systems lack a synthetic handle for electronic coupling.…”
Section: The Bigger Picturementioning
confidence: 99%
See 1 more Smart Citation
“…Nanoscale control over chromophore position is challenging in proteins due to their structural complexity and limitations in mutagenesis. [20][21][22] Instead, synthetic model systems that position chromophores have been developed, including metal-organic frameworks, 8,23 viral proteins, [24][25][26] self-assembled molecular aggregates, [27][28][29][30] and conjugated polymers. 31 However, these systems lack a synthetic handle for electronic coupling.…”
Section: The Bigger Picturementioning
confidence: 99%
“…While the impact of the bath on exciton dynamics had been well established theoretically, [97][98][99] previous experiments were limited to the impact of the bath on individual excitonic states. 24 Chromophore-DNA constructs open the door to varying the system-bath coupling for chromophore aggregates, and thus achieving the full nanoscale control required to direct exciton dynamics.…”
Section: Dependence Of Energy-transfer Efficiency On Dna Scaffoldmentioning
confidence: 99%
“…Scientists usually used chemical modification or biological genetic recombination to construct functional protein nanomaterials. Francis et al site-specifically modified TMV coat proteins with chromophore pairs, and found TMV disks could not only prevent the aggregation-induced quench of chromophores but also greatly improved FRET transfer efficacy (Delor et al, 2018). If introducing GPx catalytic centers on TMV via site-directed gene mutagenesis, the reengineered nanostructures showed ultrahigh catalytic activity and stability (Hou et al, 2012).…”
Section: Reconstructionmentioning
confidence: 99%
“…These studies demonstrate that complementary geometric shapes and non-covalent interactions within a protein binding pocket can be used to create a conformationally determined, lock-and-key specificity for photosensitizer integration within protein host matrices. Further, investigations of photosynthetic biohybrid designs for light-harvesting have demonstrated that chiral linkages can be used to create sterically-constrained, chromophore-protein couplings that function to enhance light-harvesting by modulating nuclear relaxation dynamics, extending excited-state lifetimes, and controlling Stokes shift energy losses (Delor et al 2018). These designed protein-chromophore interactions are anticipated to mimic those functioning in native photosynthetic light-harvesting proteins.…”
Section: Introductionmentioning
confidence: 99%